(untitled) (Cadernos de Sociomuseologia, 2026)
This text presents the passage between the New Museology (Desvallées 1992 and 1994) and Social Museology, but also the specificities of the latter, firmly anchored in Latin America’s commitment to making the museum an instrument at the service of social transformation (Duarte Cândido in Capanema, Ruoso and Duarte Cândido, 2025). We seek to demonstrate the importance of moments such as the Santiago de Chile Round Table (1972) and the First Workshop of the International Movement for a New Museology (MINOM) (Quebec 1984) for the renewal of Museology and for the affirmation of ideas and practices that continue to reverberate in what is now Social Museology. We also address its decolonial aspects and its reach in museums in times of crisis such as the COVID-19 pandemic and climate changes. Finally, we show that even though major challenges and resistance persist in more conservative parts of the museum environment, the last 10 years have been generous in signs of international recognition of Social Museology, such as its influence on the Recommendation for the Protection and Promotion of Museums and Collections in view of their Diversity and their Role in Society (UNESCO 2015); the presence of actors from the field from more than 15 countries at the MINOM Conference in Catania, Sicily, Italy (2024); and especially the creation of an International Committee on this theme at the International Council of Museums with (SOMUS/ICOM). Keywords: New Museology, Social Museology, MINOM